A method for forming an ultra-thin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support

CN123000385APending Publication Date: 2026-10-30BEIHANG UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610947095.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]本发明针对超薄单面光电解铜箔在成形过程中易失稳、表面易损伤、单层材料难以稳定进入模具以及成形后支撑层不易分离等问题,通过对铜箔毛面进行微喷丸处理,并结合后续退火工艺调节材料状态,再利用可拆卸临时粘结层将上下覆板与中间铜箔构建为层合支撑复合结构,随后实施压边拉深成形,最终经除胶分离获得目标成形件

Benefits of technology

(1)本发明显著拓宽了超薄铜箔的成形极限,有效抑制成形缺陷:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123000385A_ABST
    Figure CN123000385A_ABST
Patent Text Reader

Abstract

The application provides a forming method of an ultra-thin single-sided photo-electrolytic copper foil based on surface strain regulation and detachable laminated support, and the flow of the method is as follows: blank preparation and smooth surface support adhesion, rough surface wet micro-blasting treatment, vacuum annealing, preparation of detachable laminated support composite structure, edge pressing deep drawing forming, interface debonding and demolding. The detachable laminated support composite structure is composed of a thermal release adhesive and a rigid cover plate. Through wet blasting surface strain regulation, vacuum annealing and edge pressing deep drawing forming under the constraint state on the rough surface of the ultra-thin single-sided photo-electrolytic copper foil, the ultra-thin single-sided photo-electrolytic copper foil component with a thickness of 10 microns to 70 microns is prepared. The component has the advantages of good surface integrity, stable profile precision and zero-stress non-destructive demolding, and can improve the forming process stability, and improve the surface quality, profile consistency and engineering application reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain control and detachable laminated support. It is applicable to the edge-pressing and deep-drawing forming of ultrathin single-sided photoelectrolytic copper foil components with thicknesses ranging from 10 micrometers to 70 micrometers. It primarily addresses the problems of wrinkling, tearing, surface damage, and difficulty in controlling forming precision during the forming process of ultrathin single-sided photoelectrolytic copper foil. This invention belongs to the field of aerospace precision manufacturing technology. Background Technology

[0002] Ultrathin single-sided photoelectrolytic copper foil is a type of thin-film metallic material that combines lightweight, electrical and thermal conductivity, and surface functional properties, making it highly valuable for applications in complex curved surface functional components, thin-walled shielding components, and locally conformal functional layers. In practical applications, this type of material typically requires not only good fit accuracy to the target curved surface after forming, but also high surface integrity and consistency to meet subsequent service or assembly requirements. For ultrathin single-sided photoelectrolytic copper foil with relatively small thickness, existing forming processes commonly suffer from problems such as wrinkling, cracking, localized thinning, contour fluctuations, and surface damage, making it difficult to meet the forming quality and stability requirements of complex curved precision components.

[0003] Single-sided photoelectrolytic copper foil exhibits significant differences in surface characteristics, with one side being relatively smooth and the other relatively rough. It also features a small overall thickness, low bending stiffness, and sensitivity to external load disturbances. In aerospace, electronics, precision heat exchange, and the manufacturing of special functional layers, this type of copper foil has high application value. It can serve as a base material for conformal electromagnetic shielding layers, microwave absorbing layers, localized heat-conducting layers, micro-heat exchange coating layers, precision flow-guiding auxiliary layers, flexible conductive connection layers, and complex curved surface sensing functional layers. In high-performance aircraft, spacecraft, electronic packaging components, and complex curved surface thermal management structures, this type of copper foil often needs to be precisely matched with the fuselage outer surface, compartment transition surface, localized flow-guiding surface, heat exchange surface, or other spatial transition surfaces. While maintaining high bonding accuracy, it must also meet functional requirements such as conductivity, thermal conductivity, or shielding, avoiding surface damage, indentations, wrinkles, or interlayer misalignment that could affect its subsequent service performance and assembly accuracy. However, during the direct stamping, deep drawing, or pressing process, ultrathin single-sided photoelectrolytic copper foil often suffers from problems such as wrinkling, instability, tearing, surface damage, and dimensional fluctuations in edge areas, curvature transition areas, or locally compressed areas due to insufficient rigidity, extremely small thickness, and uneven local stress. Furthermore, the difference in surface condition between the smooth and rough sides of the single-sided photoelectrolytic copper foil makes it more sensitive to mold contact conditions, edge pressing methods, and interlayer support conditions, easily leading to insufficient local bonding, damage to surface functional surfaces, or decreased contour consistency after forming. This affects the structural accuracy, surface quality, and functional realization of complex curved surface components. Therefore, designing a forming method for ultrathin single-sided photoelectrolytic copper foil based on surface strain control and detachable laminated support has become a key step in realizing the engineering application of related complex curved surface functional components.

[0004] Currently, there are some patents and literature both domestically and internationally related to the forming of thin plates, thin-walled sheet metal parts, and metal foils, as well as surface treatment, temporary fixing, and demolding. However, most of these focus on temporary fixing processes for general thin plates, conventional sheet metal parts, ordinary surface-treated objects, or electronic components, and are difficult to directly apply to the high-precision, complex curved surface forming of ultra-thin single-sided photoelectrolytic copper foil with a thickness of less than 70 micrometers. Related and similar literature is as follows: Chinese patent CN 104010810 A discloses a copper foil composite, a molded body, and a method for manufacturing the same. This method yields a copper foil composite consisting of stacked copper foil and resin layers, which exhibits excellent processability and long-term stable corrosion resistance and electrical contact performance, even under harsh (complex) deformations such as pressing (different from uniaxial bending), preventing copper foil breakage. However, the method focuses on the structure of the copper foil composite itself and its corrosion resistance and electrical contact performance, rather than addressing surface strain control before forming ultra-thin single-sided photoelectrolytic copper foil, or the issue of low-damage separation of the support layer after forming.

[0005] Chinese Patent CN 103042109 A discloses a high-frequency vibration-assisted foil micro-drawing forming device and method, aiming to solve the problem that it is difficult to draw foil with low material strength into cylindrical parts with small diameters. Utilizing the micro-drawing forming device of this invention, with the assistance of high-frequency vibration, improves the friction of the flange portion during micro-drawing, suppresses crack initiation, and can significantly improve the micro-drawing performance of foil. This method mainly focuses on improving forming equipment and friction conditions, but does not address the pre-control of the surface state of the ultra-thin single-sided photoelectrolytic copper foil before forming, nor does it form a complete process route combining detachable lamination support during the forming stage with post-forming separation.

[0006] Chinese Patent CN 101589174 A discloses a surface treatment method for metals. The method involves shot peening the surface of a base metal with dissimilar metal particles, creating a dissimilar metal film. An electron beam is then irradiated onto the surface of the base metal with the dissimilar metal film formed during the shot peening process, thereby bonding the dissimilar metal film to the base metal. This method achieves a simple and efficient way to reliably bond various metals to the surface of various base metals in an alloy state. However, this method is primarily used for base metal surface bonding and surface modification, and is not designed for the forming process of ultra-thin single-sided photoelectrolytic copper foil. It does not consider issues such as overall warping, edge instability, and surface functional surface protection during subsequent deep drawing of ultra-thin copper foil.

[0007] In recent years, there has been considerable research on surface strengthening of conventional metal sheets, thin sheet stamping, temporary fixing materials, and peeling processes. However, there are still few dedicated process methods for ultra-thin single-sided electrolytic copper foil, including surface strain control before forming, improved subsequent forming stability through detachable laminated supports, and effective separation of the support layer after forming. These methods are insufficient to meet the manufacturing requirements of ultra-thin single-sided electrolytic copper foil in precision forming processes, which demand stability in forming, surface integrity, interlayer coordination, and consistent dimensions. Therefore, it is necessary to propose a dedicated process method to address the problems of surface sensitivity, poor stability in a free state, uneven load transfer after lamination support, and difficulty in removing the support layer after forming in the forming process of ultra-thin single-sided electrolytic copper foil. By controlling the surface strain of the copper foil before forming and combining it with a detachable laminated support to form a stable composite, followed by subsequent forming and separation treatments, the stability of the forming process of ultra-thin single-sided electrolytic copper foil can be improved, thereby enhancing its surface quality, contour consistency, and reliability in engineering applications. Summary of the Invention

[0008] This invention addresses the problems of instability, surface damage, difficulty in stable entry of single-layer material into the mold, and difficulty in separating the support layer after forming in ultra-thin single-sided photoelectrolytic copper foil during the forming process. The method involves micro-shot peening the rough surface of the copper foil, followed by annealing to adjust the material state. A removable temporary adhesive layer is then used to construct a laminated support composite structure with the upper and lower cover plates and the middle copper foil. This is followed by edge pressing and deep drawing, and finally, the target formed part is obtained through adhesive removal and separation. This method improves the stability of ultra-thin single-sided photoelectrolytic copper foil during the forming process, reduces surface damage and forming defects, and improves the contour accuracy and forming consistency of the component.

[0009] This invention proposes a method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain control and detachable laminated support. The process flow is as follows: vacuum adsorption support of the smooth surface of ultrathin single-sided photoelectrolytic copper foil → wet micro-shot peening of the rough surface → vacuum annealing → preparation of detachable laminated support composite structure → edge pressing and deep drawing → glue removal and separation → finished product.

[0010] The technical solution of the present invention will be described in detail below: Step 1: Blank preparation and smooth surface support bonding: Ultra-thin single-sided photoelectrolytic copper foil with a thickness of 10 to 70 micrometers is selected as the blank. The selected copper foil should have good surface flatness and thickness uniformity, and be free of creases, scratches, and oxide spots. The copper foil is cut according to the unfolded dimensions of the target part, with a process allowance of 2 to 5 mm reserved at the outer edge. The smooth surface of the copper foil is bonded to a rigid vacuum chuck with a micropore diameter of 0.1 to 0.5 mm. The rigid vacuum chuck is a flat vacuum adsorption support platform with micropores evenly distributed on its working surface to form a uniform planar adsorption constraint on one side of the smooth surface of the copper foil. The vacuum system is turned on to maintain the vacuum degree at -0.08 to -0.095 MPa. Uniform constraint over the entire area is achieved through atmospheric pressure difference. The in-plane rigid constraint provided by vacuum adsorption prevents the copper foil from bulging as a whole or becoming locally unstable during subsequent impact processes.

[0011] Step 2: Wet shot blasting treatment of the rough surface: Wet micro-shot peening was performed on the rough surface of copper foil in an adsorption-fixed state to achieve surface strain control. Micro-ceramic beads with a diameter of 10–50 micrometers were used as the peening medium. Driven by a low-pressure fluid of 0.03–0.15 MPa, the rough surface was subjected to micro-energy impact at a spray angle of 50–65° and a spray distance of 80–150 mm for 10–30 seconds. Plastic deformation was used to pre-control the rough surface of the copper foil, providing stable initial conditions for subsequent annealing and edge-drawing. After shot peening, the copper foil was transferred to a flat support plate for subsequent vacuum annealing to maintain a flat and supported state during the heat treatment process.

[0012] Step 3: Vacuum annealing: The strain-controlled copper foil is then annealed. The annealing process takes place in a vacuum environment at 280–320°C for 3–5 hours, followed by furnace cooling. This stabilizes the dislocation structure on the surface, resulting in a more uniform distribution of residual compressive stress and reducing the risk of instability and cracking due to localized stress concentration during subsequent edge-drawing and forming processes.

[0013] Step 4: Fabrication of a detachable laminated support composite structure: Annealed copper foil is used as the core material and is combined with upper and lower aluminum cladding plates to form a detachable laminated support composite structure. The composite structure, from top to bottom, consists of an upper cladding plate, a heat-release adhesive layer, an ultra-thin single-sided photoelectrolytic copper foil, another heat-release adhesive layer, and a lower cladding plate. The upper cladding plate has a thickness of 0.5–0.8 mm, and the lower cladding plate has a thickness of 1.0–1.5 mm. A heat-release adhesive layer is placed between the copper foil and the cladding plates as a temporary bonding layer. Pre-bonding and compaction are performed at room temperature under a pressure of 0.05–0.3 MPa. During subsequent forming, the heat-release adhesive flows smoothly with the laminated material, maintaining interlayer fixation between the copper foil and the cladding plates while also providing load transfer and buffering. The resulting laminated structure macroscopically exhibits high bending stiffness, effectively distributing local load peaks during forming and reducing the adverse effects of interlayer misalignment, local voids, and sudden stress changes on forming quality.

[0014] Step 5: Blanket pressing and deep drawing: The laminated support composite structure obtained in step 4 is positioned in a blank holder drawing die and drawn under blank holder conditions. The blank holder drawing die includes a die cavity, a punch, and a blank holder ring; the laminated support composite structure is placed in the area above the die cavity and deformed in a controlled manner by the punch under the constraint of the blank holder ring. During the forming process, the lower cover plate is close to the die cavity surface, and the upper cover plate is close to the punch and blank holder ring side. The copper foil in the middle gradually adheres to the target surface under the coordinated action of the upper and lower cover plates and the hot-release adhesive. Under the constraint of a blank holder force of 10-30kN, the drawing is carried out at a speed of 3-10mm / s. The copper foil is in a constrained flow state under the rigid support of the upper and lower cover plates and the load transfer effect of the hot-release adhesive. The rigid support of the upper and lower cover plates and the coordinated load transfer effect of the adhesive layer effectively reduce the instability tendency of the copper foil in the free state, reduce the risk of wrinkling, tearing, local thinning and surface damage during the drawing process, and improve the consistency and contour accuracy of the curved surface forming.

[0015] Step 6: Interface loss of adhesion and demolding: After the edge-pressing and deep-drawing process is completed, the laminated support composite structure undergoes adhesive removal to separate the upper and lower cover plates from the intermediate copper foil forming part. After forming, the entire part is heated to 90–120°C and held at that temperature for 10–20 minutes. During this time, the micro-expansion particles within the heat-peeling adhesive layer undergo irreversible physical expansion, resulting in a sharp reduction in the interfacial bonding area and a permanent drop in bond strength. After the part cools naturally to room temperature, the upper and lower cover plates can be peeled off from the copper foil forming part under relatively low additional stress. Finally, the rough and smooth surfaces are ultrasonically cleaned with acetone or ethanol to remove residual adhesive, obtaining a finished ultra-thin copper foil curved surface with a complete surface.

[0016] The ultrathin single-sided photoelectrolytic copper foil forming parts prepared by this invention have advantages such as good forming stability, small surface damage, little interlayer slippage and stable contour dimensions under the combined action of surface strain control and detachable lamination support. They can meet the application requirements of high precision, low damage and high reliability forming for curved surface functional components, precision thin-walled components and conformal functional layer components.

[0017] Compared with the prior art, the present invention has the following advantages: (1) This invention significantly expands the forming limit of ultra-thin copper foil and effectively suppresses forming defects: In existing technologies, single-layer ultrathin copper foil is prone to local instability, wrinkling, or tensile fracture during stamping and deep drawing due to its extremely low bending stiffness. This invention, through the rough-surface wet micro-shot peening treatment in step 2, introduces a gradient-distributed residual compressive stress field along the thickness direction of the copper foil, effectively counteracting the local tensile stress generated during subsequent forming processes. The laminated support structure prepared in step 4 significantly improves the overall equivalent stiffness of the blank, placing the copper foil in a constrained flow state during forming, effectively reducing the risk of defects such as wrinkling, tearing, and excessive local thinning. This invention constructs a dedicated process route based on its forming characteristics, thus better adapting to the high-precision, low-damage, and high-consistency manufacturing requirements of ultrathin single-sided photoelectrolytic copper foil components.

[0018] (2) This invention achieves precise pre-control of the surface state of ultrathin single-sided photoelectrolytic copper foil by controlled shot peening based on rigid support constraints: By performing controlled shot peening on the rough surface and maintaining a tight fit between the smooth surface and a rigid vacuum adsorption support plate, pre-regulation of the surface state of ultrathin single-sided photoelectrolytic copper foil was achieved. This step, performed under rigid support conditions, reduces the risk of overall deformation and local instability of the copper foil during shot peening. The post-shot peening annealing process further improves the overall stability of the copper foil while retaining the surface regulation effect.

[0019] (3) This invention provides better protection for the surface quality of smooth surfaces: The surface quality of ultrathin copper foil is crucial to its conductivity, shielding, and service performance. In step 1, this invention utilizes vacuum adsorption to fix the surface, avoiding damage to the surface from mechanical clamps. During the deep drawing process in step 5, the copper foil is fixed between the upper and lower cover plates and the temporary adhesive layer, avoiding direct contact with the mold surface. This effectively isolates the surface from scratches, indentations, and marks caused by microscopic defects in the mold, ensuring the integrity and cleanliness of the formed part's surface.

[0020] (4) The detachable laminated support composite structure prepared by the present invention can achieve non-destructive demolding of ultra-thin parts under low additional stress conditions, and has good process stability and surface contour accuracy: A temporary bonding material with isotropic rheological properties is selected to ensure that the bonding layer maintains interlayer fixation during molding while also flowing in coordination with the deformation of the sheet material under load, thus balancing fixation and load transfer. The heating and debonding process not only achieves physical debonding but also acts as a low-temperature stress-relieving annealing process, accelerating the release of residual elastic stress inside the molded part, significantly reducing elastic rebound after demolding, and improving the dimensional stability and mold fit consistency of the parts.

[0021] (5) The process parameters of the present invention are highly controllable and have a wide range of applications: By adjusting the micro-shot peening pressure, annealing conditions, and hot-release adhesive parameters, precise forming processes can be customized for ultra-thin foils of different specifications and materials. This not only applies to single-sided photoelectrolytic copper foil but also provides a high-yield, low-cost industrial solution for manufacturing other high-precision, highly sensitive thin-film functional components. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the process method of the present invention.

[0023] Figure 2 This is a schematic diagram of the cross-section of a deep drawing process with blank holder.

[0024] Figure 3 This is a schematic diagram of the formed part. Detailed Implementation

[0025] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings and examples. Examples are used to illustrate the invention and not to limit it. The scope and core content of the invention are defined by the claims.

[0026] Example 1: 70-micron thick single-sided photoelectrolytic copper foil: Step 1: Blank Preparation and Smooth Surface Support Bonding: A 70-micron thick single-sided photoelectrolytic copper foil with good surface flatness and thickness uniformity, free from creases, scratches, and oxide spots, is selected as the blank. The blank size is laser-cut to 400mm x 400mm. The smooth surface of the copper foil is bonded to a rigid vacuum chuck with a micropore diameter of 0.3mm. The vacuum system is activated to maintain a vacuum level of -0.08MPa, achieving uniform constraint over the entire area through atmospheric pressure difference, and utilizing the in-plane rigid constraint provided by vacuum adsorption.

[0027] Step 2: Wet micro-shot peening of the rough surface: The rough surface of the copper foil in its adsorption and fixation state is subjected to wet micro-shot peening. Micro-ceramic beads with a diameter of 50 micrometers are used as the peening medium. Driven by a low-pressure fluid of 0.15 MPa, the rough surface is subjected to micro-energy impact at a 60° spray angle and a spray distance of 150 mm for 30 seconds. After shot peening, the copper foil is transferred to a flat support plate for subsequent vacuum annealing to maintain its flat and supportive state during the heat treatment process.

[0028] Step 3: Vacuum annealing: Anneal the copper foil in a vacuum environment at a temperature of 300℃, hold for 4 hours, and then cool it in the furnace.

[0029] Step 4: Preparation of a detachable laminated support composite structure: Annealed copper foil is used as the core material to prepare a detachable laminated support composite structure with upper and lower aluminum cladding plates. The composite structure, from top to bottom, consists of an upper cladding plate, a heat-release adhesive layer, an ultra-thin single-sided photoelectrolytic copper foil, another heat-release adhesive layer, and a lower cladding plate. The upper cladding plate is 0.7 mm thick, and the lower cladding plate is 1.4 mm thick. Heat-release adhesive is used as a temporary bonding layer between the copper foil and the cladding plates. Pre-bonding and compaction are performed at room temperature under a pressure of 0.2 MPa.

[0030] Step 5: Blanket drawing and forming: Position the laminated support composite structure in the blanket drawing die, such as... Figure 2 As shown, deep drawing is performed under blank holder conditions. During the forming process, the upper and lower cover plates maintain interlayer coordinated deformation with the intermediate copper foil under the action of a temporary adhesive layer, allowing the ultrathin single-sided photoelectrolytic copper foil to gradually adhere to the target surface under supported and constrained conditions. Deep drawing is performed at a speed of 6 mm / s under a blank holder force of 30 kN.

[0031] Step 6: Interface De-adhesion and Demolding: After the edge-pressing and deep drawing process, the laminated support composite structure is de-adhesive-removed to separate the upper and lower cover plates from the middle copper foil forming part. After forming, the entire part is heated to 120℃ and held for 20 minutes. After the part cools naturally to room temperature, the upper and lower cover plates can be peeled off from the copper foil forming part under low additional stress. Finally, acetone is used to ultrasonically clean both the rough and smooth surfaces to remove residual adhesive, obtaining a finished ultra-thin copper foil curved surface with a complete surface.

[0032] Example 2: 50-micron thick single-sided photoelectrolytic copper foil: Step 1: Blank Preparation and Smooth Surface Support Bonding: A 50-micron thick single-sided photoelectrolytic copper foil with good surface flatness, thickness uniformity, and no creases, scratches, or oxide spots is selected as the blank. The blank size is laser-cut to 400mm x 400mm. The smooth surface of the copper foil is bonded to a rigid vacuum chuck with a micropore diameter of 0.1mm. The vacuum system is activated to maintain a vacuum level of -0.08MPa. Uniform constraint is achieved over the entire area through atmospheric pressure difference, utilizing the in-plane rigid constraint provided by vacuum adsorption.

[0033] Step 2: Wet micro-shot peening of the rough surface: The rough surface of the copper foil in its adsorption and fixation state is subjected to wet micro-shot peening. Micro-ceramic beads with a diameter of 30 micrometers are used as the peening medium. Driven by a low-pressure fluid of 0.05 MPa, the rough surface is subjected to micro-energy impact at a 60° spray angle and a spray distance of 120 mm for 20 seconds. After shot peening, the copper foil is transferred to a flat support plate for subsequent vacuum annealing to maintain its flat and supportive state during the heat treatment process.

[0034] Step 3: Vacuum annealing: Anneal the copper foil in a vacuum environment at a temperature of 300℃, hold for 4 hours, and then cool it in the furnace.

[0035] Step 4: Preparation of a detachable laminated support composite structure: Annealed copper foil is used as the core material to prepare a detachable laminated support composite structure with upper and lower aluminum cladding plates. The composite structure, from top to bottom, consists of an upper cladding plate, a heat-release adhesive layer, an ultra-thin single-sided photoelectrolytic copper foil, another heat-release adhesive layer, and a lower cladding plate. The upper cladding plate is 0.5 mm thick, and the lower cladding plate is 1.0 mm thick. Heat-release adhesive is used as a temporary bonding layer between the copper foil and the cladding plates. Pre-bonding and compaction are performed at room temperature under a pressure of 0.1 MPa.

[0036] Step 5: Edge-clamping and deep drawing: The laminated support composite structure is positioned in the edge-clamping and deep drawing die, and deep drawing is performed under edge-clamping conditions. During the forming process, the upper and lower cover plates maintain interlayer coordinated deformation with the intermediate copper foil under the action of the temporary adhesive layer, allowing the ultra-thin single-sided photoelectrolytic copper foil to gradually adhere to the target surface under supported and constrained conditions. Deep drawing is performed at a speed of 6 mm / s under the constraint of an edge-clamping force of 30 kN.

[0037] Step 6: Interface De-adhesion and Demolding: After the edge-pressing and deep drawing process, the laminated support composite structure is de-adhesive-removed to separate the upper and lower cover plates from the middle copper foil forming part. After forming, the entire part is heated to 120℃ and held for 20 minutes. After the part cools naturally to room temperature, the upper and lower cover plates can be peeled off from the copper foil forming part under low additional stress. Finally, acetone is used to ultrasonically clean both the rough and smooth surfaces to remove residual adhesive, obtaining a finished ultra-thin copper foil curved surface with a complete surface.

[0038] Example 3: 10-micron thick single-sided photoelectrolytic copper foil: Step 1: Blank Preparation and Smooth Surface Support Bonding: A 10-micron thick single-sided photoelectrolytic copper foil with good surface flatness, thickness uniformity, and no creases, scratches, or oxide spots is selected as the blank. The blank size is laser-cut to 400mm x 400mm. The smooth surface of the copper foil is bonded to a rigid vacuum chuck with a micropore diameter of 0.1mm. The vacuum system is activated to maintain a vacuum level of -0.09MPa. Uniform constraint is achieved over the entire area through atmospheric pressure difference, utilizing the in-plane rigid constraint provided by vacuum adsorption.

[0039] Step 2: Wet micro-shot peening of the rough surface: The rough surface of the copper foil in its adsorption and fixation state is subjected to wet micro-shot peening. Micro-ceramic beads with a diameter of 10 micrometers are used as the peening medium. Driven by a low-pressure fluid of 0.03 MPa, the rough surface is subjected to micro-energy impact at a spray angle of 55° and a spray distance of 130 mm for 10 seconds. After shot peening, the copper foil is transferred to a flat support plate for subsequent vacuum annealing to maintain its flat and supportive state during the heat treatment process.

[0040] Step 3: Vacuum annealing: Anneal the copper foil in a vacuum environment at a temperature of 300℃, hold for 3 hours, and then cool it in the furnace.

[0041] Step 4: Preparation of a detachable laminated support composite structure: Annealed copper foil is used as the core material to prepare a detachable laminated support composite structure with upper and lower aluminum cladding plates. The composite structure, from top to bottom, consists of an upper cladding plate, a heat-release adhesive layer, an ultra-thin single-sided photoelectrolytic copper foil, another heat-release adhesive layer, and a lower cladding plate. The upper cladding plate is 0.5 mm thick, and the lower cladding plate is 1.0 mm thick. Heat-release adhesive is used as a temporary bonding layer between the copper foil and the cladding plates. Pre-bonding and compaction are performed at room temperature under a pressure of 0.05 MPa.

[0042] Step 5: Edge-clamping and deep drawing: The laminated support composite structure is positioned in the edge-clamping and deep drawing die, and deep drawing is performed under edge-clamping conditions. During the forming process, the upper and lower cover plates maintain interlayer coordinated deformation with the intermediate copper foil under the action of the temporary adhesive layer, allowing the ultra-thin single-sided photoelectrolytic copper foil to gradually adhere to the target surface under supported and constrained conditions. Deep drawing is performed at a speed of 3 mm / s under the constraint of a 12 kN edge-clamping force.

[0043] Step 6: Interface De-adhesion and Demolding: After the edge-pressing and deep drawing process, the laminated support composite structure is de-adhesive-removed to separate the upper and lower cover plates from the middle copper foil forming part. After forming, the entire part is heated to 90℃ and held for 10 minutes. After the part cools naturally to room temperature, the upper and lower cover plates can be peeled off from the copper foil forming part under low additional stress. Finally, acetone is used to ultrasonically clean the rough and smooth surfaces to remove residual adhesive, obtaining a finished ultra-thin copper foil curved surface with a complete surface.

Claims

1. A method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support, characterized in that, The steps include the following: Step 1: Blank preparation and smooth surface support bonding: Ultra-thin single-sided photoelectrolytic copper foil with smooth surface and uniform thickness, free from creases, scratches and oxide spots is selected as the blank. The copper foil is cut according to the unfolded size of the target part, and the smooth surface of the copper foil is bonded to the rigid vacuum chuck. Step 2: Wet shot blasting treatment of the rough surface: Wet micro-shot peening is applied to the rough surface of copper foil in an adsorption-fixed state to achieve surface strain control; Step 3: Vacuum annealing: The strain-controlled copper foil is then annealed. Step 4: Fabrication of a detachable laminated support composite structure: Annealed copper foil is used as the core material and is combined with aluminum upper and lower cladding plates to form a detachable laminated support composite structure. Step 5: Blanket pressing and deep drawing: The laminated support composite structure obtained in step 4 is positioned in a blank holder drawing die and drawn under blank holder conditions. The blank holder drawing die includes a die cavity, a punch and a blank holder ring. The laminated support composite structure is placed in the area above the die cavity and is driven by the punch to deform in a controlled manner into the die cavity under the constraint of the blank holder ring. Step 6: Interface loss of adhesion and demolding: After the edge-pressing and deep drawing process is completed, the adhesive is removed from the laminated support composite structure to separate the upper and lower cover plates from the middle copper foil forming part, thereby obtaining an ultra-thin copper foil curved surface finished product with a complete surface.

2. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 1, an ultra-thin single-sided photoelectrolytic copper foil with a thickness of 10 micrometers to 70 micrometers is selected as the blank, with a process allowance of 2 to 5 mm reserved at the outer edge; the smooth surface of the copper foil is bonded to a rigid vacuum chuck with a micropore diameter of 0.1 to 0.5 mm. The rigid vacuum chuck is a flat vacuum adsorption support platform with micropores evenly distributed on the working surface, which is used to form a uniform adsorption constraint on one side of the smooth surface of the copper foil.

3. A method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1 or 2, characterized in that, In step 1, the vacuum system is turned on to maintain the vacuum level at -0.08 to -0.095 MPa. The atmospheric pressure difference is used to achieve uniform constraint over the entire area. The in-plane rigid constraint provided by vacuum adsorption is used to prevent the copper foil from bulging or becoming unstable in a localized manner during the subsequent impact process.

4. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 2, the shot peening medium consists of micro-ceramic beads with a diameter of 10–50 micrometers. Driven by a low-pressure fluid of 0.03–0.15 MPa, the surface is subjected to micro-energy impact at a spray angle of 50–65° and a spray distance of 80–150 mm for 10–30 s. Plastic deformation is used to pre-regulate the surface of the copper foil to provide stable initial conditions for subsequent annealing and edge drawing.

5. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 3, the annealing temperature is 280-320℃ in a vacuum environment, and the temperature is held for 3-5 hours before being cooled in the furnace. This stabilizes the dislocation structure of the surface layer, makes the residual compressive stress field more uniformly distributed, and reduces the risk of instability and cracking caused by local stress concentration during the subsequent edge-pressing and deep drawing process.

6. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 4, the composite structure consists of an upper cover plate, a heat-release adhesive layer, an ultra-thin single-sided photoelectrolytic copper foil, a heat-release adhesive layer, and a lower cover plate from top to bottom. The upper cover plate has a thickness of 0.5 to 0.8 mm, and the lower cover plate has a thickness of 1.0 to 1.5 mm. A heat-release adhesive layer is provided between the copper foil and the cover plate as a temporary bonding layer.

7. A method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1 or 6, characterized in that, In step 4, pre-bonding and compaction are performed at room temperature, with pre-pressing under a pressure of 0.05 to 0.3 MPa. The hot-release adhesive flows in coordination with the laminated sheet during the subsequent forming process, maintaining the interlayer fixation between the copper foil and the cover plate, while also bearing a certain load transfer and buffering effect.

8. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 5, during the forming process, the lower cover plate is close to the concave mold surface, and the upper cover plate is close to the punch and the pressure ring side. The copper foil in the middle gradually adheres to the target surface under the coordinated action of the upper and lower cover plates and the hot peeling adhesive. Under the constraint of the pressure force of 10 to 30 kN, the drawing is carried out at a speed of 3 to 10 mm / s. Under the rigid support of the upper and lower cover plates and the load transfer action of the hot peeling adhesive, the copper foil is in a constrained flow state.

9. The method for forming ultrathin single-sided photoelectrolytic copper foil based on surface strain regulation and detachable laminated support according to claim 1, characterized in that, In step 6, after the forming is completed, the entire part is heated to 90-120°C and held for 10-20 minutes. At this time, the micro-expansion particles in the heat-peeling adhesive layer undergo irreversible physical expansion, resulting in a sharp reduction in the interface bonding area and a permanent drop in bonding strength. After the part cools naturally to room temperature, the upper and lower cover plates are peeled off from the copper foil forming part. Finally, acetone or ethanol is used to ultrasonically clean the rough and smooth surfaces to remove residual adhesive and obtain an ultra-thin copper foil curved surface finished product with a complete surface.

10. An ultrathin single-sided photoelectrolytic copper foil forming part based on surface strain regulation and detachable laminated support, characterized in that: The ultrathin copper foil curved surface with a thickness of 10 micrometers to 70 micrometers is prepared by using the process steps described in claim 1.

Citation Information

Patent Citations

  • Metal surface treatment method

    CN101589174A

  • Device and method for high-frequency vibration assisted micro-deep drawing forming of foil boards

    CN103042109A

  • Copper-foil composite, formed body, and manufacturing method therefor

    CN104010810A